A Three-Year Review of Emergency Department Admissions - Op HERRICK 4 to 9. Issue Volume 157:Issue (2011)Supplement 3 (1st September 2011) - Stalker, Andrew; Ollerton, J; Everington, S; Russell, R; Walker, C; White, S
Abstract : Objectives: This paper describes the key themes in presentations to the Emergency Department (ED) of the UK Field Hospital throughout the three-year period of April 2006 to April 2009 (Op HERRICK 4-9). Methods: Electronic ED attendance records held in the Operational Emergency Department Attendance Register (OpEDAR) were analysed with validation by Defence Analytical Services Agency and commentary by ADMEM clinical staff. Results: This paper discusses absolute numbers of emergency department attendances of which there were 11, 158 recorded over the study period. It does not compare them to personnel at risk or operational tempo. Of these attendances, 59.7% (n=6, 666) were UK military. Explosive injuries (15.2%, n=1, 699), particularly Improvised Explosive Devices, increased throughout the period as did gunshot wounds (7.3%, n=809). Battle injuries represented 23.3% (n=2, 602) attendances and had a fatality rate of 10.9%. 38.8% (n=4, 327) of attendances were non-battle injuries and had a fatality rate of 0.4%. There were no fatalities in the 34.1% (n=3, 800) attendances for disease. 315 fatalities were recorded (this figure relates to all attendances – not just UK personnel) with 90.2% (n=284) due to battle injuries. 59.4% (n=187) were due to explosives and 28.9% (n=91) due to gunshot wounds. Conclusions: Over the period, the hospital's workload was characterised by an increase in explosive and gunshot injuries. In this role, the hospital met its obligation of responding to traumatic battle injury in support of fighting power and morale. Equally, the hospital faced a high proportion of attendances for non-battle injury and illness, and by patients from the local population. Extrapolation of data enables accurate medical planning and pre-deployment training and facilitates preparation for current operations.